Green one-step synthesis of ZnO/cellulose nanocrystal hybrids with modulated morphologies and superfast absorption of cationic dyes - Guan, Ying; Yu, Hou-Yong; Abdalkarim, Somia Yassin Hussain; Wang, Chuang; Tang, Feng; Marek, Jaromir; Chen, Wei-Lai; Militky, Jiri; Yao, Ju-Ming (International journal of biological macromolecules, 2019)
Zinc oxide/cellulose nanocrystal (ZnO/CNC) hybrids with modulated morphologies were prepared by using bamboo CNC as templates via green one-step technique. The effect of pH values on the morphology, microstructure, thermal stability, antibacterial efficiency and dye absorption kinetics of hybrids were investigated. A possible mechanism for various hybrid morphologies at different pH values was provided. All the samples exhibited high antibacterial ratios of 91.4%-99.8% against both Escherichia coli and Staphylococcus aureus. ZnO/CNC8.5 gave quick removal efficiency with high dye removal ratios in methylene blue (MB, 93.55%) and malachite green (MG, 99.02%), especially >91.47% and 97.85% within 5 min. The absorption capacity could reach up to 46.77 mg/g for MB and 49.51 mg/g for MG. Besides, absorption kinetics showed that the absorption behavior followed the pseudo-second-order kinetic model (R2 > 0.99996). Such ZnO/CNC hybrids show outstanding and low-cost adsorbent for efficient absorption of cationic dyes in wastewater treatment field.
Keywords: Coloring Agents; celulosa; technologie zelené chemie; Temperature; čištění vody; Water Purification; Green Chemistry Technology; Staphylococcus aureus; Nanoparticles; Cationic dye absorption; antibakteriální látky; nanočástice; Rosaniline Dyes; odpadní voda; Waste Water; Hydrogen-Ion Concentration; Morphological modulation; Escherichia coli; Absorption, Physicochemical; Cellulose; methylenová modř; oxid zinečnatý; koncentrace vodíkových iontů; kinetika; Wastewater; techniky syntetické chemie; Anti-Bacterial Agents; barvicí látky; Methylene Blue; Zinc Oxide; teplota; Chemistry Techniques, Synthetic; ZnO/cellulose nanocrystal hybrids; fyzikální absorpce; Kinetics; rosanilinová barviva